Optimalisasi Pengolahan Sampah Menggunakan Biopori Dan Bank Sampah Untuk Mengurangi Pencemaran Lingkungan - Muzzaki, Rafie H.; Dzakirah, Hafizhah; Sekarsari, Karina I.; Savitri, Leila S.; Putri, Najwa A.; Abizar, Anugrah R.; Rusydi, Rifqi H.; Fahriyah, Samirah A.; Rahmat, Rofif I.; Susanto, Ferry; Widowaty, Yeni (Universitas Muhammadiyah Yogyakarta, 2025)
The Thematic Regular Community Service Program Group 166 of Universitas Muhammadiyah Yogyakarta (UMY) conducted a community service program in Klaci II Hamlet, Margoluwih, Seyegan, Sleman, Yogyakarta. The program focused on organic and inorganic waste management to address environmental pollution issues. Two primary approaches were implemented: the creation of biopore infiltration holes and the establishment of a waste bank. This initiative aimed to improve waste management practices, reduce the volume of waste sent to landfills, and create a cleaner and more sustainable environment. The methods employed included three main stages: education, demonstration, and consistency. The education stage involved raising public awareness about the benefits of biopores and waste banks, including flood risk reduction and soil quality improvement. Demonstrations were conducted through hands-on activities in creating biopore infiltration holes in several neighborhoods within Klaci II Hamlet. The consistency stage involved regular monitoring of biopore holes and evaluating their environmental and economic impacts. The waste bank program was designed to encourage active community participation by offering incentives for sorting and recycling waste with economic value. This activity was held weekly, involving various community groups to foster habits of recycling and proper waste management. The results showed increased community awareness regarding waste management, the use of organic waste as compost, and reduced environmental pollution. Through a community-based approach, this program successfully fostered behavioral changes in waste management practices in Klaci II Hamlet. Beyond providing direct benefits to the local community, this model has the potential to be replicated in other regions as a sustainable solution for addressing waste management issues. By collaborating with the community, the program not only enhanced environmental quality but also strengthened communal independence in preserving the environment.